ORA1, a Zebrafish Olfactory Receptor Ancestral to All Mammalian V1R Genes, Recognizes 4-Hydroxyphenylacetic Acid, a Putative Reproductive Pheromone - Behrens, Maik (American Society for Biochemistry and Molecular Biology, 2014)
The teleost v1r-related ora genes are a small, highly conserved olfactory receptor gene family of only six genes, whose direct orthologues can be identified in lineages as far as that of cartilaginous fish. However, no ligands for fish olfactory receptor class A related genes (ORA) had been uncovered so far. Here we have deorphanized the ORA1 receptor using heterologous expression and calcium imaging. We report that zebrafish ORA1 recognizes with high specificity and sensitivity 4-hydroxyphenylacetic acid. The carboxyl group of this compound is required in a particular distance from the aromatic ring, whereas the hydroxyl group in the para-position is not essential, but strongly enhances the binding efficacy. Low concentrations of 4-hydroxyphenylacetic acid elicit increases in oviposition frequency in zebrafish mating pairs. This effect is abolished by naris closure. We hypothesize that 4-hydroxyphenylacetic acid might function as a pheromone for reproductive behavior in zebrafish. ORA1 is ancestral to mammalian V1Rs, and its putative function as pheromone receptor is reminiscent of the role of several mammalian V1Rs as pheromone receptors.